Shallot cultivation originated from true shallot seed (TSS) on Andisols enriched with various ameliorants - Aprianto, Fahmi; Arifin, Mahfud; Sofyan, Emma Trinurani (Kultivasi, 2023)
Application of soil ameliorants is important to improve Andisols properties and increase shallot productivity. The research objective is to determine the kind of ameliorant which the best effect on the growth and productivity of shallots originating from TSS in Andisols Lembang, West Java. The experiment was conducted in Margahayu Research Station, Lembang, West Java from January to May 2021. A randomized block design (RBD) with 6 treatments and 5 replications was set up in the field. Treatments include control (no ameliorant), 20 tons/ha of horse manure, 10 tons/ha of rice straw compost, 10 tons/ha of bamboo leaf compost, 10 tons/ha of husk biochar, and 5 kg/ha humic acid. The results showed that vegetative performance and yield of true shallot seed-based shallot variety of Trisula in Andisols enriched with rice straw compost was higher than in other ameliorant treatments. Additionally, nutrient uptake in rice straw compost treatment was also higher than in other ameliorant treatments.